Effect of Fungal Infection on the Fatty Acid Composition of Peanut (Arachis hypogaea L.) Oil - Enas Nasr,; Ahlaam Mowloud,; Abtisam Alharari, (AlQalam Journal of Medical and Applied Sciences, 2026)
Peanut (Arachis hypogaea L.) is an important oilseed crop cultivated extensively in many tropical and subtropical regions. Fungal pathogens and root-knot nematodes represent major constraints to peanut production, causing significant yield losses and potentially affecting seed quality. This study investigated the fatty acid composition of peanut oil extracted from healthy seeds and seeds naturally infected with root-rot fungi (Rhizoctonia solani, Fusarium solani, Aspergillus niger, and Aspergillus flavus) and root-knot nematode (Meloidogyne javanica). Gas chromatographic analysis revealed nine fatty acids in peanut oil, with six identified as palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1n9c), linoleic acid (C18:2n6c), arachidic acid (C20:0), and cis-11-eicosenoic acid (C20:1). The major fatty acids in both healthy and infected seeds were oleic, linoleic, and palmitic acids. Infection resulted in decreased palmitic acid (from 13.14% to 12.75%) and linoleic acid (from 36.60% to 33.87%) content, while oleic acid increased from 40.36% in healthy seeds to 43.14% in infected seeds. These alterations in fatty acid profile may affect oil stability, nutritional quality, and industrial applications. This study provides important insights into how pathogen infection can modify the lipid composition of peanut oil.